2011
DOI: 10.1093/jxb/erq443
|View full text |Cite
|
Sign up to set email alerts
|

Drought alters timing, quantity, and quality of wood formation in Scots pine

Abstract: Drought has been frequently discussed as a trigger for forest decline. Today, large-scale Scots pine decline is observed in many dry inner-Alpine valleys, with drought discussed as the main causative factor. This study aimed to analyse the impact of drought on wood formation and wood structure. To study tree growth under contrasting water supply, an irrigation experiment was installed in a mature Scots pine (Pinus sylvestris L.) forest at a xeric site in a dry inner-Alpine valley. Inter- and intra-annual radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
133
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(165 citation statements)
references
References 49 publications
27
133
1
4
Order By: Relevance
“…In contrast, in years when precipitation was abnormally low and temperatures were higher than usual, most trees formed narrow rings. Our findings are in line with recent detailed intra-annual studies of P. sylvestris tree-ring formation Oberhuber and Gruber 2010;Eilmann et al 2011), which confirmed previous conclusions (Antonova et al 1995;Rigling et al 2001; Eilmann et al Thabeet et al 2009) that drought stress hinders cell production in P. sylvestris and thus may have profound effects on tree-ring width. The effect of moisture deficiency on tree-ring width in our study sites was most pronounced during several known drought periods-namely in 1917-1919, 1945-1948 and 1984-1994.…”
Section: Altitude Influence On Climate-growth Relationshipssupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, in years when precipitation was abnormally low and temperatures were higher than usual, most trees formed narrow rings. Our findings are in line with recent detailed intra-annual studies of P. sylvestris tree-ring formation Oberhuber and Gruber 2010;Eilmann et al 2011), which confirmed previous conclusions (Antonova et al 1995;Rigling et al 2001; Eilmann et al Thabeet et al 2009) that drought stress hinders cell production in P. sylvestris and thus may have profound effects on tree-ring width. The effect of moisture deficiency on tree-ring width in our study sites was most pronounced during several known drought periods-namely in 1917-1919, 1945-1948 and 1984-1994.…”
Section: Altitude Influence On Climate-growth Relationshipssupporting
confidence: 93%
“…Water shortage and stress are known to strongly influence cell metabolism and division and thus have an impact on tree-ring formation (Whitmore and Zahner 1967;Antonova et al 1995). In analogy with studies of tree-ring formation in coniferous species at sites with similar ecological conditions, we expect that latewood cell production at our sites starts in July, and cell wall thickening and lignification continues into October (Gindl et al 2001;Camarero et al 1998;Rigling et al 2001;Eilmann et al 2011), but may be terminated earlier due to dry conditions (Thabeet et al 2009;Gruber et al 2010;Eilmann et al 2011). Thus, droughts in July and August may considerably influence the stages of latewood cell production and development.…”
Section: Tree-ring Features and Climate Extremesmentioning
confidence: 84%
See 3 more Smart Citations